A study on sporadic renal cell carcinoma in young adults, our institutional experience - Prakash JVS; Thiruvarul PV; Vetrichandar S; Mohamadali Basitali Sayyad (Asian Journal of Medical Sciences, 2024)
Background: Renal cell carcinoma (RCC) accounts for around 2–3% of all adult malignant neoplasms. Most RCC instances are sporadic, with about 4–6% being familial. Sporadic RCC is uncommon in young patients under 45, accounting for 3–7% of all instances. We report our experience with sporadic RCCs in young adults between the age of 20 and 45 years. Aims and Objectives: The aim is to study clinical presentation, evaluation, management, and prognosis of sporadic RCC in young adults. Materials and Methods: A retrospective review of 22 patients diagnosed with sporadic RCC between ages 20 and 45 years during a period of 7 years from 2016 to 2022 was performed at Government Stanley Medical College. Demographic details such as age, gender, clinical condition, blood investigations, radiological imaging, and histopathological evaluation were conducted. Patients were assessed for long-term outcomes by comparing metastasis and lymph node involvement with survival outcomes. Results: The mean age at diagnosis was 37 years. Most patients belong to lower socioeconomic status (54.5%), Tumors were detected incidentally in 9 patients (41%) and were symptomatic in 13 (59%). Around 87% of patients were not having any associated comorbidities. The average duration of presenting complaints in symptomatic patients was 41 days. About 59% of patients were smokers or chewing tobacco before diagnosis. Renal biopsy was performed in 27% of patients before definitive surgery. The difference in prognosis was found to be insignificant between patients who were asymptomatic at the time of diagnosis compared to patients who were symptomatic. The tumor stage and grade had a significant impact on survival. The mean postoperative follow-up was 38 months. Conclusion: The result of our study shows that sporadic RCC does not behave aggressively in young adults. The most important determinants in prognosis are tumor stage and histological grade. The type of surgical procedure does not affect the overall outcome.